The 3-2-3 Detective Agency in The disappearance of Dave Warthog - Robinson, Fiona, 1965- (New York : Amulet Books, 2009)
Five animal friends decide to form a detective agency in Whiska City, where they investigate the rash of disappearances linked to a poodle beauty salon.
Booklist
Kirkus Review
Publisher's Weekly
4.1
3-6
3-6
Keywords: Animals -- Comic books, strips, etc. -- Juvenile fiction; Missing persons -- Comic books, strips, etc. -- Juvenile fiction; Private detectives -- Comic books, strips, etc. -- Juvenile fiction; Animals -- Fiction; Cartoons and comics; Missing persons -- Fiction; Mystery and detective stories; Private detectives -- Fiction; Animals -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Graphic novels; Missing persons -- Comic books, strips, etc. -- Fiction; Mystery graphic novels; Private detectives -- Comic books, strips, etc. -- Fiction; Graphic novels; Mystery comic books, strips, etc